Esters with water. - Getzen, Forrest W.; Hefter, G. T.; Maczynski, Andrzej (Solubility data series, 1992)
This is the second volume in this series devoted to the solubility of esters with water. It includes solubility data for binary systems containing an ester and water up to the end of 1988. The critical evaluations were all prepared by one author and an introductory section has been included to elaborate the philosophy and methodology followed in the evaluations.